Corporate Governance and Corporate Social Responsibility Disclosures: Evidence from the Listed Companies in Sri Lanka - Sarmila, K.; Niresh, J.A. (SOUTH ASIAN JOURNAL OF FINANCE, 2023)
Purpose: The primary objective of this study is to investigate the nexus between corporate governance and corporate social responsibility disclosure in Sri Lankan listed firms. Design/Methodology/Approach: Corporate governance was evaluated using the following criteria: board size, board independence, role duality, women representation, audit committee size, and ownership concentration. The Global Reporting Initiative (GRI) methodology was utilized to assess Corporate Social Responsibility Disclosure (CSRD) using content analysis. This study collects balanced panel data from 44 Sri Lankan listed firms over a five-year period, from 2018 to 2022. Because of their highly regulated nature, the banking, finance, insurance, and investment trust industries were omitted from the sample. All of the information was gathered from yearly reports published on the Colombo Stock Exchange's website in Sri Lanka. Findings: Test results suggest that board size, independence, and women representation have no significant relationship with CSRD. Role Duality, Audit Committee Size and Ownership Concentration exhibit a significant association with CSRD. Moreover, the mean value of the CSRD is 44.56 percent for the selected listed companies in Sri Lanka. Originality: This study contributes to determining the extent to which companies have adhered to the GRI as a widely acknowledged disclosure framework. It provides value to the company's management in order for them to make better judgments on whether the firms should involve them in more corporate governance disclosures in order to raise the degree of CSR to enhance transparency and to promote stakeholders' well-being. The outcome also has ramifications for regulatory agencies in developing obligatory reporting requirements for all listed firms to comply with the GRI framework.
Keywords: Corporate social responsibility disclosure; Corporate governance; Global Reporting Initiative listed companies; Sri Lanka